A Health-Communication Teaching Module - Casasbuenas Duarte, Luis; Hernández Carmona, David; Gómez Dávila, Joaquín Guillermo (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This article introduces a teaching module on Health Communication, which arises from the perceived needs in our environment and studies by Nacer Center. Communication and life are so closely related that are considered inseparable concepts, therefore, teaching and development on this field is relatively new, not only adds significant elements of personal and professional training for our graduates from Universidad de Antioquia; it also allows to directly contribute to the improvement of health care assistance, to achieve quality, respect and opportunity needed - and deserved - by the people or communities seeking to promote health, prevent illness, or solve health problems.